Regulatory T Cell-Derived Exosomes: Possible Therapeutic and Diagnostic Tools in Transplantation - Agarwal, Akansha; Fanelli, Giorgia; Letizia, Marilena; Tung, Sim Lai; Boardman, Dominic; Lechler, Robert; Lombardi, Giovanna; Smyth, Lesley A. (Frontiers in Immunology, 2014)
Exosomes are extracellular vesicles released by many cells of the body. These small vesicles play an important part in intercellular communication both in the local environment and systemically, facilitating in the transfer of proteins, cytokines as well as miRNA between cells. The observation that exosomes isolated from immune cells such as dendritic cells (DCs) modulate the immune response has paved the way for these structures to be considered as potential immunotherapeutic reagents. Indeed clinical trials using DC derived exosomes to facilitate immune responses to specific cancer antigens are now underway. Exosomes can also have a negative effect on the immune response and exosomes isolated from regulatory T cells (Tregs) and other subsets of T cells have been shown to have immune suppressive capacities. Here we review what is currently known about Treg derived exosomes and their contribution to immune regulation, as well as highlighting their possible therapeutic potential for preventing graft rejection, and their possible use as diagnostic tools to assess transplant outcome.